从新马华人比较研究到新马华文文学比较研究 = From the comparative study of ethnic Chinese in Singapore and Malaysia to the comparative study of Chinese literature in Malaysia and Singapore (A preface) - 李元瑾 Lee, Guan Kin (新加坡青年书局 = the Youth Book Co., 2015)
Abstract not available.